VAKSIN-Based Blended Learning in Moodle on Students’ Geometry Problem-Solving Skills - Suriyah, Puput; Dewi Utami, Anita; Mayasari, Novi; Nadiya Abu Hasan, Nurul; Indriani, Ari (Phenomenon : Jurnal Pendidikan MIPA, 2024)
As institutions adapt to the "new normal" era, educators are challenged to design learning experiences that remain engaging, effective, and accessible. To respond to this need, the VAKSIN (Video Animation for Online Learning Systems) approach was developed as part of a blended learning model. This study aimed to determine whether blended learning using VAKSIN in Moodle is more effective than the online learning model in improving student problem solving. The study employed a posttest-only control design on students' bisectors in a geometry course. A saturated sampling technique was used to select all population members as samples. There are 80 subjects and data collection methods, including documentation and testing. Final semester testscores are used to test the sample class's normality, homogeneity, and balance before being subjected to treatment. Hypothesis testing was conducted using a t-test. The results of the data analysis revealed that the t-value for the experimental and control groups was tcount = 3.191084707 and ttable = 1.99084707. Since tcount > ttable, the null hypothesis (H0) was rejected. Thus, it can be concluded that blended learning using VAKSINN is effective in improving students' problem-solving abilities in learning mathematics on the geometry of lines and angles.